2022
DOI: 10.3390/ijms23042165
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase-2-Linked Glycolytic Overload and Unscheduled Glycolysis—Driver of Insulin Resistance and Development of Vascular Complications of Diabetes

Abstract: The recent discovery of the glucose-induced stabilization of hexokinase-2 (HK2) to proteolysis in cell dysfunction in model hyperglycemia has revealed a likely key initiating factor contributing to the development of insulin resistance and vascular complications in diabetes. Consequently, the increased flux of glucose metabolism without a change in the expression and activity of glycolytic enzymes produces a wave of increased glycolytic intermediates driving mitochondrial dysfunction and increased reactive oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 142 publications
1
22
0
Order By: Relevance
“…This revealed that the increased concentration of triosephosphates and formation of MG is not produced by inhibition of glyceraldehyde-3-phosphate dehydrogenase, as was proposed earlier [ 1 ], but rather by increased dysregulated or ‘unscheduled’ early-stage glycolysis arising from increased accumulation and activity of hexokinase-2 (HK2) without similar change in activity of other glycolytic enzymes [ 18 , 20 ]. This produces a wave of increased glycolytic intermediates, accounting for increased formation of MG and also activation of protein kinase C and hexosamine pathways [ 41 ]— Figure 1 . The cause of the increased HK2 activity was stabilization of HK2 to proteolysis by increased binding of glucose to the C-terminal active site during increased cytosolic hyperglycemia, masking a degradation motif linked to chaperone-mediated autophagy [ 18 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This revealed that the increased concentration of triosephosphates and formation of MG is not produced by inhibition of glyceraldehyde-3-phosphate dehydrogenase, as was proposed earlier [ 1 ], but rather by increased dysregulated or ‘unscheduled’ early-stage glycolysis arising from increased accumulation and activity of hexokinase-2 (HK2) without similar change in activity of other glycolytic enzymes [ 18 , 20 ]. This produces a wave of increased glycolytic intermediates, accounting for increased formation of MG and also activation of protein kinase C and hexosamine pathways [ 41 ]— Figure 1 . The cause of the increased HK2 activity was stabilization of HK2 to proteolysis by increased binding of glucose to the C-terminal active site during increased cytosolic hyperglycemia, masking a degradation motif linked to chaperone-mediated autophagy [ 18 ].…”
mentioning
confidence: 99%
“…In HK2-linked unscheduled glycolysis in hyperglycemia, increased formation of ROS is a consequence rather than a cause of metabolic dysfunction and is one of multiple dysfunctional pathways. This may explain why clinical evaluation of antioxidants for therapy of diabetic complications has been disappointing [ 41 ]. A better approach emerged when it was found that tRES-HESP corrected increased HK2 protein and activity by off-target effects mediated by Nrf2-mediated increased expression of glucose-6-phosphate dehydrogenase, decreasing cellular concentration of G6P, transcriptional signaling by Mondo A/Mlx/G6P and expression of HK2.…”
mentioning
confidence: 99%
“…tRES induces increased activity of NAD-dependent deacetylase, Sirtuin-1, and may thereby promote the removal of an inhibitory acetylation of Nrf2 to increase transcriptional activity [ 43 , 76 ]. The mechanism of activation of Nrf2 by tRES-HESP has been discussed elsewhere in this Special Series [ 77 ]. HESP is a partial agonist which is likely due to inhibitory nuclear acetylation of Nrf2 blocking a high E max .…”
Section: Development and Applications Of Glyoxalase 1 Inducers For Im...mentioning
confidence: 99%
“…An increase in expression of G6PD was implicated in a decrease in transcriptional activity of G6P/mlx/Mondo A complex regulating genes with a functional carbohydrate response element (ChRE)—including HK2, TXNIP, and other glycolytic and lipogenic genes. This corrected multiple pathways of metabolic dysfunction in model hyperglycemia in HAECs and PDLFs in vitro [ 7 , 28 ] and was implicated in the development of insulin resistance, vascular complications of diabetes, diabetic embryopathy, and ischemia-reperfusion injury in vivo [ 77 , 81 ]. Functional genomic studies with tissue-selective activation of Nrf2 by partial knockdown of Keap1 in the obesogenic HFD-fed mouse model of insulin resistance indicated that selective activation of Nrf2 in skeletal muscle and the liver corrected insulin resistance and dysglycemia, respectively [ 82 ].…”
Section: Development and Applications Of Glyoxalase 1 Inducers For Im...mentioning
confidence: 99%
See 1 more Smart Citation